Miocene woods of the Janggi Basin in Korea: Implications for paleofloral changes - Lim, Jong-Deock; Jeong, Eun-Kyoung; Kim, Kyungsik; Suzuki, Mitsuo; Paik, In Sung; Kim, Haang-Mook (Geosciences Journal, 2010)
Eleven taxa of fossil woods — two gymnosperms and nine dicotyledons — were identified from 59 specimens collected from the Lower Coal-bearing Formation of the Janggi Group at Shinjeong-ri in Donghae-myeon, Pohang City, Gyeongsangbukdo, Korea. One new taxon, Fraxinus oligocenica , was discovered and identified for the first time in the Korean Peninsula. Along with the previous study, 25 Miocene wood taxa, in total, have been described from the Lower and Upper Coal-bearing formations of the Janggi Group. A considerable number of specimens of Wataria were collected in this study. Wataria is an extinct genus of the Sterculiaceae, and the determination of its true identity is an interesting paleobotanical subject. There may be a possibility that the quantity and diversity of Wataria spp. was greater in the Korean Peninsula than in the Japanese Archipelago. Thus, we suggested that the Miocene deposits in Pohang City would be better places for elucidating the real identity of Wataria than in Japan. Coalbearing formations in which fossil woods occur intervene between the Geumgwangdong Formation and the Duho Formation in which abundant fossil leaves occur. In the combined fossil-wood and fossil-leaf data from these formations, we found a transitiontype flora situated between the well-known Aniai-type and Daijimatype floras in Japan.